Resin composition and radio frequency antenna-related component
Patent Information
- Application Number
- JP2020190339
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-16
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-11-16
Smart Images

Figure 0007630257000001 
Figure 0007630257000002 
Figure 0007630257000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a radio-frequency antenna-related member. [Background technology]
[0002] Many thermoplastic resins are used as resin molding materials in a wide variety of applications, including electronic and electrical parts, office automation equipment parts, audiovisual equipment parts, and automotive parts. In recent years, there has been a demand for improved dielectric properties and further improved fluidity during hot melt processing in resin parts for information and communication devices, etc., in order to meet the demands of higher communication speeds and smaller precision. In particular, there is a strong demand for materials with low dielectric constants for electronic component boards and high dielectric constants for antenna members. In this situation, the addition of high dielectric materials to resin materials used for antenna members and the like has been proposed in order to improve the dielectric constant, and titanium dioxide in particular is widely used due to its balance between price and dielectric constant (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-24326 A [Patent Document 2] JP 2011-116870 A [Patent Document 3] Japanese Patent Application Publication No. 11-60743 Summary of the Invention [Problem to be solved by the invention]
[0004] As described above, Patent Documents 1 to 3 disclose titanium dioxide-added resin compositions. However, although the resin compositions obtained by these techniques have improved dielectric properties, they have further problems in terms of the balance with other physical properties such as fluidity and impact resistance.
[0005] An object of the present invention is to provide a resin composition and a radio-frequency antenna-related member that have a good balance between high dielectric properties, fluidity, and impact resistance. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that a resin composition to which a polyphenylene ether resin, a polyethylene resin, a hydrogenated block copolymer, and titanium dioxide are added in specific proportions has excellent dielectric properties, fluidity, and impact resistance, which led to the present invention.
[0007] That is, the present invention is as follows. [1] A thermoplastic resin mixture containing (a) 10 to 50 mass% of a polyphenylene ether resin, (b) 40 to 85 mass% of a polyethylene resin, and (c) 5 to 20 mass% of a hydrogenated block copolymer; (d) 10 to 200 parts by mass of titanium dioxide relative to 100 parts by mass of the thermoplastic resin mixture; Including Mu-ki fat composition A high-frequency antenna-related member formed by . [2] The component (a) is a polyphenylene ether resin having a mass ratio of polyphenylene ether resin / polystyrene resin of 100-10 / 0-90. High frequency antenna related materials . [3] The component (b) is a high-density polyethylene. High frequency antenna related materials . [4] The component (d) is rutile titanium dioxide. High frequency antenna related materials . [5] The (d) titanium dioxide optionally contains a treatment agent; (d) Any of [1] to [4], in which the mass ratio of titanium dioxide is 92 mass% or more relative to 100 mass% of titanium dioxide. High frequency antenna related parts. Effect of the Invention
[0008] According to the present invention, it is possible to provide a resin composition having excellent dielectric properties, flowability and impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present invention is not limited to the following embodiment, and can be carried out in various modifications within the scope of the gist of the present invention.
[0010] The resin composition of the present embodiment contains a thermoplastic resin mixture containing (a) 10 to 50 mass % of a polyphenylene ether resin, (b) 40 to 85 mass % of a polyethylene resin, and (c) 5 to 20 mass % of a hydrogenated block copolymer, and contains (d) 10 to 200 mass parts of titanium dioxide per 100 mass parts of the thermoplastic resin mixture. With the above-described configuration, the resin composition of the present embodiment can exhibit an even better balance of physical properties in terms of dielectric characteristics, fluidity, and impact resistance. In this specification, (a) polyphenylene ether resin may be referred to as “component (a)”, (b) polyethylene resin may be referred to as “component (b)”, (c) hydrogenated block copolymer may be referred to as “component (c)”, and (d) titanium dioxide may be referred to as “component (d)”.
[0011] The components of the resin composition of the present embodiment will be described below. [Resin composition] <Thermoplastic resin mixture> The resin composition of the present embodiment contains (a) a polyphenylene ether resin, (b) a polyethylene resin, and (c) a hydrogenated block copolymer in a thermoplastic resin mixture. The total mass proportion of the components (a) to (c) in the above thermoplastic resin mixture is preferably 90 mass% or more, more preferably 95 mass% or more, relative to 100 mass% of the thermoplastic resin mixture, and may be 100 mass% (i.e., the thermoplastic resin mixture is a mixture consisting only of the components (a) to (c)). The thermoplastic resin mixture is a mixture consisting of only a plurality of types of thermoplastic resins.
[0012] (a) Polyphenylene ether resin The polyphenylene ether-based resin that can be used as component (a) can include polyphenylene ether (sometimes referred to as "PPE" in this specification) and a polystyrene-based resin (for example, an atactic polystyrene-based resin). The PPE-based resin may be a mixed resin made of PPE and a polystyrene-based resin (for example, an atactic polystyrene-based resin), or may be a resin made of only PPE. Since the polyphenylene ether resin contains PPE, the resin composition of the present embodiment has even more excellent heat resistance.
[0013] Examples of the PPE include homopolymers having a repeating unit structure represented by the following formula (1) and copolymers having a repeating unit structure represented by the following formula (1). The above PPE may be used alone or in combination of two or more kinds. [ka] In the above formula (1), R 1 , R 2 , R 3 , and R 4 are each independently a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a haloalkyl group, an aminoalkyl group, a hydrocarbyloxy group, and a halohydrocarbyloxy group in which at least two carbon atoms separate the halogen atom from the oxygen atom.
[0014] From the viewpoints of fluidity, toughness, and chemical resistance during processing, the PPE preferably has a reduced viscosity of 0.15 to 2.0 dL / g, more preferably 0.20 to 1.0 dL / g, and even more preferably 0.30 to 0.70 dL / g, as measured using a chloroform solution having a concentration of 0.4 g / dL at 30° C. using an Ubbelohde viscometer.
[0015] Examples of the PPE include, but are not limited to, homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether); copolymers such as copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol and 2-methyl-6-butylphenol); and the like. Among these, from the viewpoints of the balance between toughness and rigidity when made into a resin composition and the ease of availability of raw materials, poly(2,6-dimethyl-1,4-phenylene ether) and copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is more preferred.
[0016] The PPE can be produced by a known method, including, but not limited to, the method of oxidatively polymerizing 2,6-xylenol using a complex of cuprous salt and amine as a catalyst by Hay, as described in U.S. Pat. No. 3,306,874, the methods described in U.S. Pat. Nos. 3,306,875, 3,257,357, 3,257,358, JP-B-17880 / 1977, JP-A-51197 / 1975, JP-A-63-152628, and the like.
[0017] The PPE may be a modified PPE obtained by reacting the homopolymer and / or the copolymer with a styrene monomer or a derivative thereof and / or an α,β-unsaturated carboxylic acid or a derivative thereof, wherein the graft or addition amount of the styrene monomer or a derivative thereof and / or the α,β-unsaturated carboxylic acid or a derivative thereof is preferably 0.01 to 10% by mass relative to 100% by mass of PPE.
[0018] Examples of the method for producing the modified PPE include a method in which the PPE is reacted in the presence or absence of a radical generator in a molten state, solution state or slurry state at a temperature of 80 to 350°C.
[0019] As the PPE, a mixture of the homopolymer and / or the copolymer and the modified PPE in any ratio may be used.
[0020] The polystyrene resin contained in component (a) is preferably an atactic polystyrene resin, and more preferably atactic polystyrene or rubber-reinforced polystyrene (high impact polystyrene, HIPS). The polystyrene resins may be used alone or in combination of two or more kinds.
[0021] As component (a), a polyphenylene ether resin in which the mass ratio (PPE / polystyrene resin) of PPE to a polystyrene resin (for example, an atactic polystyrene resin) is 100 / 0 to 10 / 90 can be used. From the viewpoints of fluidity, heat resistance, and impact resistance, the mass ratio (PPE / polystyrene resin) of such a mixture is more preferably 98 / 2 to 20 / 80, even more preferably 95 / 5 to 30 / 70, and particularly preferably 95 / 5 to 50 / 50.
[0022] The mass proportion of the (a) polyphenylene ether resin in 100 mass% of the above thermoplastic resin mixture is 10 to 50 mass%, preferably 15 to 48 mass%, and more preferably 20 to 45 mass%, from the viewpoints of heat resistance and fluidity. In order to achieve a better balance between fluidity and impact resistance, the mass proportion of the (a) polyphenylene ether resin in 100 mass% of the resin composition of this embodiment is preferably 3.2 to 45.5 mass%, more preferably 5.0 to 43.6 mass%, and even more preferably 6.7 to 40.9 mass%.
[0023] ((b) Polyethylene resin) The polyethylene resin of component (b) has a density of 0.93 to 0.97 g / cm 3 High density polyethylene, density 0.91~0.93g / cm 3 Low density polyethylene, density 0.90~0.95g / cm 3 Linear low density polyethylene, density 0.90g / cm 3 and copolymers of two or more compounds of ethylene and a compound selected from other α-olefins such as propylene, for example, ethylene / propylene copolymers, ethylene / butene-1 copolymers, ethylene / octene copolymers, and propylene / ethylene (random, block) copolymers. Among these, from the viewpoints of heat resistance, impact resistance, availability, and cost, high density polyethylene and low density polyethylene are excellent, and a mixture of high density polyethylene and low density polyethylene may also be used. In particular, high density polyethylene is preferred from the viewpoint of further improving heat resistance while maintaining dielectric properties, fluidity, and impact resistance.
[0024] The polyethylene resin of component (b) preferably has an MFR of 0.1 g / 10 min or more and 40 g / 10 min or less, more preferably 0.2 g / 10 min or more and 30 g / 10 min or less, and even more preferably 0.4 g / 10 min or more and 20 g / 10 min or less. When the MFR is higher than 0.1 g / 10 min, the molecular weight is sufficiently high, so that the resin composition of the present embodiment has excellent impact resistance, and when the MFR is 40 g / 10 min or less, the resin composition of the present embodiment has excellent fluidity without a significant decrease in impact resistance. The MFR of the polyethylene resin, component (b), is a value measured in accordance with ISO1 133:2005, Code D.
[0025] The mass proportion of the (b) polyethylene resin in 100% by mass of the above thermoplastic resin mixture is 40 to 85% by mass, preferably 40 to 80% by mass, and more preferably 50 to 75% by mass, from the viewpoints of impact resistance and fluidity. In order to achieve a better balance between fluidity and impact resistance, the mass proportion of the (b) polyethylene resin in 100 mass% of the resin composition of this embodiment is preferably 13.3 to 77.3 mass%, more preferably 13.3 to 72.7 mass%, and even more preferably 16.7 to 68.2 mass%.
[0026] ((c) Hydrogenated block copolymer) In the resin composition of the present embodiment, (c) a hydrogenated block copolymer is used as the admixture. The hydrogenated block copolymer of component (c) emulsifies and disperses the polyphenylene ether resin (a) in the matrix of the polyethylene resin (b), and further imparts impact resistance to the resin composition.
[0027] The hydrogenated block copolymer which is component (c) is preferably a hydrogenated block copolymer obtained by hydrogenating a block copolymer consisting of at least two polymer blocks A mainly composed of a vinyl aromatic compound and at least one polymer block B mainly composed of a conjugated diene compound. The blocks contained in component (c) may have the same structure or different structures.
[0028] The term "based on" in the polymer block A based on a vinyl aromatic compound means that, in 100% by mass of the polymer block, at least 50% by mass of the structural units are derived from an aromatic vinyl compound, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0029] The same applies to the term "mainly composed of" in the polymer block B mainly composed of a conjugated diene compound, meaning that, in 100% by mass of polymer block B, at least 50% by mass is a structural unit derived from a conjugated diene compound, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0030] For example, even if a polymer block A mainly made of a vinyl aromatic compound contains a small amount of structural units derived from a conjugated diene compound or other compounds at random, if more than 50 mass % of the block is formed from structural units derived from a vinyl aromatic compound, it is considered to be a polymer block A mainly made of a vinyl aromatic compound. The same applies to the polymer block B mainly made of a conjugated diene compound.
[0031] Examples of the vinyl aromatic compound include styrene, α-methylstyrene, vinyltoluene, etc., and one or more compounds selected from these may be used, with styrene being particularly preferred.
[0032] Examples of the conjugated diene compound include butadiene, isoprene, piperylene, 1,3-pentadiene, etc. One or more compounds selected from these can be used. Among these, butadiene, isoprene, and combinations thereof are preferred, and butadiene is particularly preferred.
[0033] The 1,2-vinyl bond content in the polymer block B mainly composed of a conjugated diene compound is preferably 5% at its lower limit, more preferably 10%, still more preferably 20%, and even more preferably 30%, from the viewpoint of suppressing peeling between the domain phase and the matrix phase and exhibiting high impact resistance in a molded article obtained by emulsifying and dispersing the polyethylene resin and the polyphenylene ether resin in the resin composition and molding the resin composition. The upper limit is preferably 60%, more preferably 50%, and even more preferably 40%. The 1,2-vinyl bond amount in the polymer block B mainly composed of a conjugated diene compound means the 1,2-vinyl bond amount or the total amount of 1,2-vinyl bond amounts and 3,4-vinyl bond amounts in the microstructure of the conjugated diene compound block portion of the block copolymer.
[0034] The structure of the hydrogenated block copolymer (c) composed of the polymer block A and the polymer block B can be, for example, AB type, ABA type, ABAB type, (AB-)n -X type (wherein n is an integer of 1 or more, and X is a reaction residue of a polyfunctional coupling agent such as silicon tetrachloride or tin tetrachloride, or a residue of an initiator such as a polyfunctional organolithium compound), ABABA type, or other structure in which block units are bonded is preferred. The (c) hydrogenated block copolymer is preferably a hydrogenated product of a styrene-butadiene block copolymer having any of the above structures.
[0035] It is important that the hydrogenated block copolymer, which is the component (c), has two or more polymer blocks A from the viewpoint of emulsion dispersibility.
[0036] (c) The mass proportion of structural units derived from styrene bonded in the hydrogenated block copolymer (styrene content) is preferably from 10 to 70 mass%, more preferably from 10 to 65 mass%, and further preferably from 10 to 60 mass%.
[0037] Further referring to the individual block structures, for example, the polymer block A mainly composed of a vinyl aromatic compound is preferably a styrene homopolymer block or a styrene and butadiene copolymer block containing more than 50 mass % of styrene, preferably 70 mass % or more, and the polymer block B mainly composed of a conjugated diene compound is preferably a butadiene homopolymer block or a butadiene and styrene copolymer block containing more than 50 mass % of butadiene, preferably 70 mass % or more.
[0038] Furthermore, the individual structures of the polymer block A mainly composed of these vinyl aromatic compounds and the polymer block B mainly composed of these conjugated diene compounds may have a random or tapered distribution of the vinyl aromatic compounds or the conjugated diene compounds in the molecular chain of each polymer block (wherein the monomer component increases or decreases along the molecular chain), and may be composed of any combination of block structures in which a portion is 100% by mass of a vinyl aromatic compound (preferably styrene) or a portion is 100% by mass of a conjugated diene compound (preferably butadiene).
[0039] When there are two or more polymer blocks A mainly made of a vinyl aromatic compound and two or more polymer blocks B mainly made of a conjugated diene compound, the polymer blocks may have the same structure or different structures.
[0040] Regarding the polymer block B mainly made of a conjugated diene compound (e.g., butadiene), (c) at least one polymer block B mainly made of a conjugated diene compound (e.g., butadiene) before hydrogenation of the hydrogenated block copolymer may have a single vinyl bond content selected from conjugated diene compounds (e.g., butadiene) having a 1,2-vinyl bond content of 5 to 60%, or may be a polymer block B mainly made of a conjugated diene compound having at least one polymer block B1 mainly made of a conjugated diene compound (e.g., butadiene) having a 1,2-vinyl bond content of 5 to 60% and at least one polymer block B2 mainly made of a conjugated diene compound (e.g., butadiene) having a 1,2-vinyl bond content of less than 1 to 5%. A block copolymer showing such a block structure can be obtained by a known polymerization method in which the 1,2-vinyl bond content is controlled based on the feed sequence of each monomer unit, as shown by A-B2-B1-A, which is adjusted, for example. In this case, however, the amount of 1,2-vinyl bonds in block B is given by {(amount of vinyl bonds of B2) × (molecular weight of B2) + (amount of vinyl bonds of B1) × (molecular weight of B1)} / {(molecular weight of B2) + (molecular weight of B1)}, and is preferably 60% or less. The aliphatic double bonds of the polymer block B mainly composed of a conjugated diene compound of the block copolymer can be subjected to a hydrogenation reaction and used as a component (c) of a hydrogenated block copolymer (e.g., a hydrogenated product of a styrene-butadiene block copolymer). The hydrogenation rate of such aliphatic double bonds is 80% or more. This hydrogenation rate can usually be determined by an infrared spectrophotometer, NMR, or the like.
[0041] In addition to having the above structure, the (c) hydrogenated block copolymer can prevent peeling between the domain phase and the matrix phase in the resin composition of the present embodiment, and from the viewpoints of heat resistance, impact resistance, and processability, it is preferable that the number average molecular weight (Mnc) of the polymer block A mainly composed of a vinyl aromatic compound (e.g., styrene) is 250,000 or less, and the number average molecular weight (MncA) of the polymer block A is 8,000 or more. (c) The number average molecular weight (Mnc) of the hydrogenated block copolymer can be measured by gel permeation chromatography (GPC). In addition, in the (c) hydrogenated block copolymer, the number average molecular weight (MncA) of the polymer block A mainly composed of a vinyl aromatic compound (e.g., styrene) can be calculated, for example, in the case of an ABA structure, based on the number average molecular weight (Mnc) of the above-mentioned (c) hydrogenated block copolymer by the following calculation formula: (MncA) = (Mnc) × ratio of bound styrene amount ÷ 2, assuming that the molecular weight distribution of the (c) hydrogenated block copolymer is 1 and further that two polymer blocks A mainly composed of styrene are present with the same molecular weight. Similarly, in the case of an ABABA type (c) hydrogenated block copolymer, it can be calculated using the formula: (MncA) = (Mnc) × ratio of bound styrene amount ÷ 3. In addition, when the sequence of the block structure of the polymer block A and the block structure of the polymer block B is clear at the stage of synthesizing the styrene-butadiene block copolymer, the number average molecular weight (Mnc) may be calculated from the proportion of the polymer block A based on the measured number average molecular weight (Mnc) of the hydrogenated block copolymer (c) without relying on the above calculation formula.
[0042] The (c) hydrogenated block copolymer may be obtained by any production method as long as it has the above-mentioned structure. Examples of known production methods include those described in JP-A-47-11486, JP-A-49-66743, JP-A-50-75651, JP-A-54-126255, JP-A-56-10542, JP-A-56-62847, JP-A-56-100840, JP-A-2004-269665, British Patent No. 1,130,770, U.S. Pat. No. 3,281,383 and U.S. Pat. No. 3,639,517, and those described in British Patent No. 1,020,720, U.S. Pat. No. 3,333,024 and U.S. Pat. No. 4,501,857.
[0043] The (c) hydrogenated block copolymer may be, in addition to the above-mentioned hydrogenated block copolymer, a modified hydrogenated block copolymer (in which 0.01 to 10 mass % of the above-mentioned α,β-unsaturated carboxylic acid or a derivative thereof is grafted or added) obtained by reacting the hydrogenated block copolymer with an α,β-unsaturated carboxylic acid or a derivative thereof (an ester compound or an acid anhydride compound, for example, maleic anhydride) in the presence or absence of a radical generator in a molten state, a solution state, or a slurry state at a temperature of 80 to 350°C, or may be a mixture of the above-mentioned hydrogenated block copolymer and a modified hydrogenated block copolymer in any ratio.
[0044] The mass proportion of the (c) hydrogenated block copolymer in 100% by mass of the above thermoplastic resin mixture is 5 to 20% by mass, preferably 5 to 18% by mass, and more preferably 5 to 15% by mass. In order to achieve a better balance between fluidity and impact resistance, the mass proportion of the (c) hydrogenated block copolymer in 100 mass% of the resin composition of this embodiment is preferably 1.7 to 18.2 mass%, more preferably 1.7 to 16.4 mass%, and even more preferably 1.7 to 13.6 mass%.
[0045] (Other thermoplastic resins) The above thermoplastic resin mixture may contain, in addition to the above-mentioned components (a) to (c), other thermoplastic resins as necessary within a range that does not impair the features and effects of this embodiment.
[0046] Examples of the other thermoplastic resins include, but are not limited to, thermoplastic elastomers other than component (c) (such as block copolymers and polyolefin-based elastomers other than the above-mentioned polyethylene resins) and thermoplastic resins other than components (a) and (b).
[0047] The mass proportion of the other thermoplastic resins in the thermoplastic resin mixture is preferably 10 mass % or less, and more preferably 5 mass % or less.
[0048] <(d) Titanium dioxide> The resin composition of the present embodiment contains titanium dioxide and thus has excellent dielectric properties.
[0049] Titanium dioxide, which is generally used as a pigment in resins and paints, is divided into two types, rutile and anatase, depending on its crystal form, with the rutile type having superior dielectric properties.
[0050] The particle shape of the titanium dioxide may be particulate or fibrous. If it is particulate, titanium dioxide having an average particle size of 0.1 to 1.5 μm can be used. If it is fibrous, fibrous titanium dioxide having an average fiber diameter of 0.2 to 1.0 μm and an average fiber length of 1 to 6 μm can be used. If the average particle size or average fiber diameter is too large or small, in a conventional single-screw or twin-screw kneader, rat holes will occur in the addition hopper, the entrained air or nitrogen will flow back at the raw material inlet of the extruder, making it difficult to add stably, making it difficult to prepare a uniform resin composition by melt kneading, and the discharge rate will decrease, resulting in a decrease in productivity. In addition, the specific surface area will increase, which may cause deterioration of the resin material. In addition, if the particle size and fiber diameter distribution is wide, blocking is likely to occur, making the addition unstable and making it difficult to prepare a uniform resin composition by melt kneading. In addition, in the case of a conventional single-screw or twin-screw kneader, there is a problem that the discharge rate is reduced and productivity is reduced. In this specification, the average particle size of titanium dioxide used can be determined by the following methods: for example, measuring in a flow cell using a laser granulometer, observing with a scanning electron microscope at a magnification of 10,000 times and measuring the diameter of 100 titanium dioxide particles, and kneading into a two-component curing epoxy resin (Araldite), preparing a thin-film slice after curing, observing with a transmission electron microscope at a magnification of 10,000 times and measuring the diameter of 100 titanium dioxide particles.
[0051] For the purpose of improving the dispersibility of titanium dioxide during production and in the resin composition, the surface of the titanium dioxide may be previously treated with an inorganic or organic treating agent. Component (d) may consist solely of titanium dioxide, or it may be titanium dioxide that has been treated with the above-mentioned treating agents (e.g., coated with the above-mentioned treating agents), or it may be a mixture thereof.
[0052] As the inorganic treatment agent, alumina, zirconia, silica, a mixture thereof, etc. are used. Silica has high water absorption, and when it is made into a resin composition, it is easily affected by moisture, such as decomposition of the resin component and poor appearance of the molded product, so that alumina and zirconia are preferred when performing inorganic treatment, and when silica is used in combination, it is preferred that the amount of silica is small. The amount of these inorganic treatment agents used may be appropriately selected and determined, but is usually 2 to 10 mass% relative to 100 mass% of the titanium dioxide contained in the titanium dioxide (d). If the content of the inorganic treatment agent is too high relative to the mass of the titanium dioxide contained in the component (d), the absorbed water contained in the inorganic treatment layer on the titanium dioxide surface may cause problems such as a decrease in strength and poor appearance of the resin molded product obtained by molding the resin composition. Conversely, if the content is too low, the improvement effect may be insufficient, such as insufficient dispersibility.
[0053] Examples of the organic treatment agent include an organic silane compound or an organic silicone compound having an alkoxy group, an epoxy group, an amino group, or a Si-H bond. From the viewpoint of dispersibility in the resin composition, adhesion to the resin component, etc., an organic silicone compound having a Si-H bond is preferable. Among them, hydrogen polysiloxane is particularly preferable. The content of these organic treatment agents is usually from 0.5 to 5% by weight, and preferably from 1 to 3% by weight, based on 100% by weight of the titanium dioxide contained in component (d).
[0054] In component (d), when component (d) is taken as 100 mass%, the total content of the above treatment agents is preferably more than 0 mass% and not more than 8 mass%, more preferably not more than 5 mass%, and particularly preferably not more than 3 mass%. In other words, the above-mentioned (d) titanium dioxide optionally contains the above-mentioned treating agent, and when the (d) titanium dioxide is taken as 100% by mass, the mass ratio of titanium dioxide (sometimes referred to as "net titanium dioxide content" in this specification) is preferably 92% by mass or more, more preferably 95% by mass or more, and particularly preferably 97% by mass or more. When the (d) component does not contain the above-mentioned treating agent, it preferably consists of titanium dioxide alone, and when the (d) component contains the above-mentioned treating agent, it preferably consists of titanium dioxide and the treating agent alone.
[0055] In the resin composition of the present embodiment, the mass proportion of (d) titanium dioxide is 10 to 200 parts by mass, and preferably 10 to 150 parts by mass, per 100 parts by mass of the thermoplastic resin mixture. The mass proportion of (d) titanium dioxide in 100 mass% of the resin composition of this embodiment is preferably 9.1 to 66.7 mass%, more preferably 9.1 to 60.0 mass%, from the viewpoint of achieving even better dielectric properties, fluidity, and impact resistance.
[0056] <Other ingredients> In addition to the components described above, the resin composition of the present embodiment may contain other components as necessary within the scope of not impairing the features and effects of the present invention. The other components may be components other than the thermoplastic resin.
[0057] The content of the other components may be 20% by mass or less when the total amount of the components (a) and (b) is taken as 100% by mass.
[0058] Examples of the other components include, but are not limited to, heat stabilizers, antioxidants, metal deactivators, crystal nucleating agents, flame retardants (organic phosphate ester compounds, ammonium polyphosphate compounds, silicone flame retardants, etc.), plasticizers (epoxidized soybean oil, polyethylene glycol, fatty acid esters, fatty acid metal salts, etc.), weather (light) resistance improvers, slip agents, inorganic or organic fillers or reinforcing materials (glass fibers, carbon fibers, polyacrylonitrile fibers, aramid fibers, etc.), various colorants, release agents, and the like.
[0059] [Method of producing resin composition] The resin composition of the present embodiment can be produced by melt-kneading components (a) to (d), and, if necessary, other thermoplastic resins and other components.
[0060] Examples of the melt kneader for melt kneading include, but are not limited to, a single screw extruder, a multi-screw extruder including a twin screw extruder, a roll, a kneader, a Brabender plastograph, a Banbury mixer, etc., and from the viewpoint of kneading properties, a twin screw extruder is particularly preferred. Specific examples include the ZSK series manufactured by WERNER & PFLEIDERER, the TEM series manufactured by Toshiba Machine Co., Ltd., and the TEX series manufactured by The Japan Steel Works, Ltd.
[0061] The melt kneading temperature in this case can be selected to be a temperature above the melting point of the crystalline resin for a crystalline resin, or above the glass transition temperature of the non-crystalline resin, at which the resin can be heated and melted and processed without difficulty, and can usually be selected from the range of 200 to 370°C.
[0062] A preferred production method using an extruder is described below. The L / D (effective barrel length / inner barrel diameter) of the extruder is preferably 20 or more and 60 or less, and more preferably 30 or more and 50 or less.
[0063] The configuration of the extruder is not particularly limited, but for example, it is preferable to provide a first raw material supply port on the upstream side with respect to the flow direction of the raw material, a first vacuum vent downstream from the first raw material supply port, a second raw material supply port downstream from the first vacuum vent (if necessary, a third and a fourth raw material supply port may be provided downstream of the second raw material supply port), and a second vacuum vent downstream from the second raw material supply port. In particular, it is more preferable to provide a kneading section upstream of the first vacuum vent, a kneading section between the first vacuum vent and the second raw material supply port, and a kneading section between the second to fourth raw material supply ports and the second vacuum vent.
[0064] The method of supplying raw materials to the second to fourth raw material supply ports is not particularly limited, but a method of supplying raw materials from a side opening of the extruder using a forced side feeder tends to provide more stable supply than a simple additive supply from the openings of the second to fourth raw material supply ports of the extruder, and is therefore preferred. In particular, when the raw materials contain powder and it is desired to reduce the generation of crosslinked products or carbonized products due to the thermal history of the resin, a method using a forced side feeder that supplies from the side of the extruder is more preferable, and a method in which forced side feeders are provided at the second to fourth raw material supply ports and the raw material powder is divided and supplied is even more preferable. When a liquid raw material is added, it is preferable to add it into the extruder using a plunger pump, gear pump or the like. The upper openings of the second to fourth raw material supply ports of the extruder can also be used as openings for venting the air being transported.
[0065] The melt-kneading temperature and screw rotation speed in the melt-kneading step of the resin composition are not particularly limited, but for crystalline resins, a temperature equal to or higher than the melting point of the crystalline resin can be selected, and for non-crystalline resins, a temperature equal to or higher than the glass transition temperature can be selected so that the resin can be heated and melted and processed without difficulty. Typically, the temperature is selected from 200 to 370°C, and the screw rotation speed is 100 to 1200 rpm.
[0066] One specific example of a method for producing the resin composition of the present embodiment using a twin-screw extruder is to feed the thermoplastic resins (a) to (c) and titanium dioxide (d) to the first raw material supply port of the twin-screw extruder, set the heat melting zone to the melting temperature of the thermoplastic resin, and melt knead at a screw rotation speed of 100 to 1200 rpm, preferably 200 to 500 rpm. The components (a) to (d) may be fed to the twin-screw extruder from the first raw material supply port of the extruder all at once as described above, or may be fed separately from the second, third, and fourth raw material supply ports.
[0067] Furthermore, when reducing the generation of crosslinked products or carbonized products due to the thermal history of the resin in the presence of oxygen, it is preferable to maintain the oxygen concentration of each process line in the addition route of each raw material to the extruder at less than 1.0% by volume. The above-mentioned addition route is not particularly limited, but a specific example can be a configuration such as a stock tank, piping, a gravimetric feeder having a refill tank, piping, a supply hopper, and a twin-screw extruder in this order. A method for maintaining such a low oxygen concentration as described above is not particularly limited, but a method of introducing an inert gas into each process line with increased airtightness is effective. Usually, it is preferable to introduce nitrogen gas to maintain the oxygen concentration at less than 1.0% by volume.
[0068] The above-described method for producing a resin composition, when the thermoplastic resin contains a powder-like component (having a volume average particle size of less than 10 μm), has the effect of further reducing residues in the screws of a twin-screw extruder when the resin composition of the present embodiment is produced using a twin-screw extruder, and further has the effect of reducing the generation of black spots, carbonized matter, and the like in the resin composition obtained by the above-described production method.
[0069] As a specific method for producing the resin composition of this embodiment, it is preferable to use an extruder in which the oxygen concentration at each raw material supply port is controlled to less than 1.0% by volume, and to carry out any one of the following methods 1 to 3. 1. A production method comprising melt-kneading all of the components (a) to (c) contained in the resin composition of the present embodiment (first kneading step), supplying all of the component (d) to the molten mixture obtained in the first kneading step, and subsequently melt-kneading the mixture (second kneading step). 2. A production method in which a part of the components (a) to (c) contained in the resin composition of this embodiment is melt-kneaded (first kneading step), a part of the component (d) is supplied to the molten mixture obtained in the first kneading step, and melt-kneading is continued (second kneading step) to obtain resin pellets, and the remaining amount of the components (a) to (c) is melt-kneaded (third kneading step), and the remaining amount of the component (d) and the pellets obtained in the second kneading step are supplied to the molten mixture obtained in the third kneading step, and melt-kneading is continued (fourth kneading step). 3. A method in which all of the components (a) to (d) contained in the resin composition of the present embodiment are melt-kneaded.
[0070] In particular, the polyphenylene ether resin, which is the raw material for component (a), and titanium dioxide, which is component (d), are in the form of powder, and have poor bite-into the extruder, making it difficult to increase the production volume per hour. Furthermore, the residence time of the resin in the extruder is long, which makes it easy for thermal degradation to occur. From the above, the resin composition obtained by the above-mentioned production methods 1 and 2 is more preferable than the resin composition obtained by production method 3, because it has improved bite-into of titanium dioxide, which is component (d), has excellent mixability of each component, can reduce decomposition due to thermal degradation, and can reduce the generation of crosslinked products and carbonized products, and can increase the production volume of the resin per hour, thereby obtaining a resin composition with excellent productivity and quality.
[0071] [Molded product] The molded article of the resin composition of the present embodiment can be produced by applying a molding method such as injection molding, metal in-mold molding, outsert molding, hollow molding, extrusion molding, sheet molding, heat press molding, rotational molding, and laminate molding, and can be widely used as a molded article such as a high-frequency antenna-related member and an information and communication device part. Among them, a high-frequency antenna-related member (for example, an antenna-related member having a frequency of 10 MHz or more) molded with the resin composition of the present embodiment is preferable. Examples of the antenna-related member include members constituting an antenna, and specifically, examples thereof include an antenna body and an antenna array. EXAMPLES
[0072] Hereinafter, the present embodiment will be described with reference to specific examples and comparative examples, but the present embodiment is not limited to these.
[0073] The methods for measuring physical properties used in the examples and comparative examples are shown below.
[0074] (1) Productivity The upper limit of the discharge amount per unit time was measured when the resin compositions of the Examples and Comparative Examples described later were produced using an extruder. The ability of titanium dioxide to be trapped in the extruder differed depending on the production method, and it was evaluated that the higher the value of the discharge amount, the more excellent the productivity.
[0075] ((2) Dielectric properties) Pellets of the resin compositions obtained in the examples and comparative examples described below were fed to a screw in-line injection molding machine set under the conditions described below to mold a flat plate (length 80 mm, width 40 mm, thickness 1.5 mm). Using this test piece, the dielectric constant (Dk) and dielectric loss tangent (Df) were measured at a frequency of 1 GHz in accordance with JIS C2138. The higher the value of the dielectric constant, the lower the value of the dielectric loss tangent, which was evaluated as being more excellent.
[0076] ((3) Liquidity) The MFR (g / 10 min) was measured under the conditions described in JIS-K7210. The higher the value, the better the fluidity.
[0077] ((4) Heat resistance) Pellets of the resin compositions obtained in the examples and comparative examples described below were fed to a screw in-line injection molding machine set under the conditions described below, and test pieces of type A were molded in accordance with ISO 10724-1. Using these test pieces, the deflection temperature under load (°C) was measured in accordance with JIS K7191-1. The higher the value, the better the heat resistance was evaluated to be.
[0078] (5) Impact resistance Pellets of the resin compositions obtained in the examples and comparative examples described below were fed to a screw in-line injection molding machine set under the conditions described below, and test pieces of type A were molded in accordance with ISO 10724-1. Using these test pieces, the Charpy impact strength (kJ / m 2 The higher the value, the better the impact resistance was evaluated.
[0079] The raw materials used in the examples and comparative examples are shown below.
[0080] <Component (a): Polyphenylene ether resin> (a1) Polyphenylene ether (reduced viscosity measured in a chloroform solution with a concentration of 0.4 g / dL at 30°C: 0.40 dL / g) (a2) High impact polystyrene (H9405 manufactured by PS Japan Co., Ltd.)
[0081] <(b) Component: Polyethylene resin> (b1): High density polyethylene (Suntech HD (registered trademark) B770 manufactured by Asahi Kasei Corporation) MFR = 0.2 (g / 10 min) (b2): High density polyethylene (Suntech HD (registered trademark) J320 manufactured by Asahi Kasei Corporation) MFR = 12 (g / 10 min) (b3): High density polyethylene (Suntech HD (registered trademark) J311 manufactured by Asahi Kasei Corporation) MFR = 26 (g / 10 min) (b4): High density polyethylene (Suntech HD (registered trademark) J300 manufactured by Asahi Kasei Corporation) MFR = 42 (g / 10 min) (b5): Low-density polyethylene (Suntech LD (registered trademark) M2004 manufactured by Asahi Kasei Corporation) MFR = 0.4 (g / 10 min) (b6): Low-density polyethylene (Suntech LD (registered trademark) M6525 manufactured by Asahi Kasei Corporation) MFR = 28 (g / 10 min) (b7): Low-density polyethylene (Suntech LD (registered trademark) M6545 manufactured by Asahi Kasei Corporation) MFR = 45 (g / 10 min) (b8): Linear low-density polyethylene (Ube Maruzen Co., Ltd. Yumerit (trademark) 015AN) MFR = 14 (g / 10 min)
[0082] <Component (c): Hydrogenated block copolymer> (c1) Hydrogenated block copolymer (Tuftec (registered trademark) H1221 manufactured by Asahi Kasei Corporation) Styrene content: 12% by mass (c2) Hydrogenated block copolymer (Tuftec (registered trademark) H1041 manufactured by Asahi Kasei Corporation) Styrene content: 32% by mass (c3) Hydrogenated block copolymer (Tuftec (registered trademark) H1051 manufactured by Asahi Kasei Corporation) Styrene content: 42% by mass (c4) Hydrogenated block copolymer (Tuftec (registered trademark) H1043 manufactured by Asahi Kasei Corporation) Styrene content 67% by mass (c5) Hydrogenated block copolymer (Tuftec (registered trademark) N504 manufactured by Asahi Kasei Corporation) Styrene content 33% by mass
[0083] <(d) Ingredient: Titanium dioxide> (d1): Titanium dioxide (manufactured by VENATOR, trade name Tioxide (registered trademark) RTC-30), average particle size 0.2 μm, net titanium dioxide content 94% by mass (d2): Fibrous titanium dioxide (manufactured by Ishihara Sangyo Kaisha, Ltd., product name TYPAQUE (registered trademark) PFR404), average fiber diameter 0.4 μm, average fiber length 3 μm, net titanium dioxide content 95% by mass
[0084] [Examples 1 to 24, Comparative Examples 1 to 7] Components (a) to (d) were mixed in the compositions shown in Tables 1 and 2, and a resin composition was produced using a twin-screw extruder ZSK-40 (manufactured by COPERION WERNER & PFLEIDERER, Germany). In this twin-screw extruder, a first raw material supply port was provided upstream of the raw material flow direction, a first vacuum vent was provided downstream of this, a second raw material supply port was provided downstream of that, and a second vacuum vent was provided further downstream of that. Using the extruder set up as described above, each component was added according to the composition and addition method shown in Tables 1 and 2, and melt-kneaded at an extrusion temperature of 250 to 320°C, a screw rotation speed of 300 rpm, and the upper limit of the discharge rate at which stable operation could be performed, to produce pellets. The resin composition pellets thus obtained were used to carry out the above-mentioned evaluations. The evaluation results are shown in Tables 1 and 2.
[0085] [Table 1]
[0086] [Table 2]
[0087] As shown in Tables 1 and 2, the resin compositions of Examples 1 to 24 were excellent in dielectric properties, fluidity and impact resistance. In comparison with the Examples, Comparative Examples 1 to 7 were inferior in any one of the dielectric properties, fluidity, heat resistance, and impact resistance, or in the balance of these physical properties. [Industrial Applicability]
[0088] The molded article molded from the resin composition of the present embodiment has excellent dielectric properties, fluidity, heat resistance, and impact resistance, and therefore the degree of freedom in designing the resin molded article can be increased. Therefore, the molded article can be used as various parts in information and communication devices and electric and electronic devices, and has industrial applicability.
Claims
1. a thermoplastic resin mixture containing (a) 10 to 50 mass% of a polyphenylene ether resin, (b) 40 to 85 mass% of a polyethylene resin, and (c) 5 to 20 mass% of a hydrogenated block copolymer; (d) 10 to 200 parts by mass of titanium dioxide relative to 100 parts by mass of the thermoplastic resin mixture; A high-frequency antenna-related component, characterized in that it is molded from a resin composition containing the above.
2. 2. The radio-frequency antenna-related member according to claim 1, wherein the component (a) is a polyphenylene ether-based resin having a mass ratio of polyphenylene ether resin / polystyrene-based resin of 100-10 / 0-90.
3. 3. The radio frequency antenna-related member according to claim 1, wherein the component (b) is a high density polyethylene.
4. 4. The radio-frequency antenna-related member according to claim 1, wherein the component (d) is rutile titanium dioxide.
5. The (d) titanium dioxide optionally contains a treatment agent; (d) The radio frequency antenna-related member according to any one of claims 1 to 4, wherein the mass ratio of titanium dioxide is 92 mass% or more relative to 100 mass% of titanium dioxide.
Citation Information
Patent Citations
Microstrip line antenna
JP1986195007A
Resin composition containing titanium dioxide
JP1999060743A
Thermoplastic resin composition and molded article
JP2004196974A
Dielectric resin composition and electronic component
JP2005146009A
Resin composition for dielectric body, and dielectric body antenna
JP2010024326A